MANAJEMEN KESISWAAN DALAM PENINGKATAN PRESTASI SISWA SEKOLAH DASAR - Dwi Asih; Enung Hasanah (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This article aims to: find out the big role of student management in improving elementary school student achievement, the importance of student management on the achievement of elementary school students. This research is a literature review that seeks to explore and restructure various related concepts from the results of previously available writing. We conducted this study by analyzing the essence of various papers on effective student management in building student achievement. Based on the results of the literature review, it is known that the role of student management in improving student achievement is seen in terms of the role of the teacher is very important, from planning to graduation or alumni, the role of student management in improving learning achievement is the involvement of regulatory efforts towards students from the time the student enters school to them. After graduating from the results of an activity that has been carried out by students, student management includes a role as one of the substances of educational management, so student management occupies a strategic position, because the central service of education, both in the setting of schooling institutions and those outside school institutions, is focused on students. School management which has an important role in the continuity of school development is student management starting from the input, process, and output of students. Student management plays a role in managing input, which is how schools and madrasah view new student admissions. The results of the discussion show that student management has a positive and significant effect on learning discipline in realizing student achievement, it can be seen from the student achievement data of the National Science Olympiad (OSN), the National Student Arts Festival and Competition (FLS2N) and the National Student Sports Olympiad (O2SN) in Wonogiri Regency Elementary School level in 2017, 2018,2019. Wonogiri Regency has actively participated in competitions in the academic and non-academic fields of students which are contested in stages. Some of the achievements have been made at the district, provincial and national levels and even have reached the international level. Educational management greatly affects the efforts to organize new students well, so that there is no overlap and time wastage in the student management process in the classroom.